Empire and antislavery : Spain, Cuba, and Puerto Rico, 1833-1874 - Schmidt-Nowara, Christopher, 1966-2015. (Pittsburgh : University of Pittsburgh Press, 1999)
Annotation In 1872, there were more than 300,000 slaves in Cuba and Puerto Rico. Though the Spanish government had passed a law for gradual abolition in 1870, slaveowners, particularly in Cuba, clung tenaciously to their slaves as unfree labor was at the core of the colonial economies. Moreover, the Spanish bourgeoisie was deeply implicated in colonial slavery as Spain was the last European power to abolish the slave trade and bonded labor in the Americas.
Introduction: Spain in the Antilles and the Antilles in Spain -- The limits of revolution: slavery and liberty in Spain and Cuba, 1833-1854 -- "Cuestión de brazos": the rise of Puerto Rican antislavery, 1840-1860 -- Free trade and protectionism: the transformation of the metropolitan public sphere, 1854-1868 -- Family, association, and free wage labor: social reform in liberal Madrid, 1854-1868 -- The colonial public sphere: the making of the Spanish Abolitionist Society, 1861-1868 -- Revolution and slavery, 1868-1870 -- "Today victory is assured": abolitionism and a new imperial order, 1870-1874 -- Conclusion: the impact and legacy of abolitionism.
Includes bibliographical references (pages 211-231) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Sociedad Abolicionista Española.; Sociedad Abolicionista Española; Antislavery movements -- Cuba; Antislavery movements -- Puerto Rico; Antislavery movements -- Spain; Spain -- Colonies -- America; Mouvements antiesclavagistes -- Cuba; Mouvements antiesclavagistes -- Porto Rico; Mouvements antiesclavagistes -- Espagne; Espagne -- Colonies -- Amérique.; 15.85 history of America; SOCIAL SCIENCE -- Slavery; Antislavery movements; Spanish colonies; America; Cuba; Puerto Rico; Spain; Sklaverei; Abschaffung; Spanien; Puerto Rico; Slavernij; Abolitionisme; Esclavage -- Abolition -- Porto Rico; Esclavage -- Abolition -- Cuba; Mouvements antiesclavagistes -- Porto Rico; Mouvements antiesclavagistes -- Cuba; Kuba; Geschichte 1833-1874.